Landscape evolution and agro-sylvo-pastoral activities on the Gorgan Plain (NE Iran) in the last 6000 years. (October 2016) - Shumilovskikh, Lyudmila S; Hopper, Kristen; Djamali, Morteza; Ponel, Philippe; Demory, Franҫois; Rostek, Frauke; Tachikawa, Kazuyo; Bittmann, Felix; Golyeva, Alexandra; Guibal, Frédéric; Talon, Brigitte; Wang, Liang-Chi; et al.
The Gorgan Plain (NE Iran) is characterized by fertile soils formed on a loess plateau and is at present primarily exploited for intensive agriculture. However, the timing and intensity of the human impact on the landscape in the past are still unclear. A sediment core, taken from the centre of the eastern Gorgan Plain in the Kongor Lake covering the major part of the Holocene from 6.1 to 0.8 ka (all ages are calibrated before present), has been studied for pollen, non-pollen palynomorphs, botanical macroremains, insects, charcoal, geochemistry, biomarkers and magnetism in order to provide new insights into the evolution of the landscape and to estimate the intensity of human activities. The data obtained suggest a dry period between 5.9 and 3.9 ka and an increase in regional humidity afterwards with a maximum between 2.7 and 0.7 ka, during the period of the Persian empires (Achaemenid through Sasanian) and the Islamic era. The eastern part of the Gorgan Plain was characterized by open steppe landscapes during the last 6 ka, which most likely were used for pasture and at least since 2.7 ka for agriculture including arboriculture. The strongest anthropogenic impact on the environment around the Kongor site is documented during the Parthian and Sasanian Empires (200 BC–651 AD) and the Islamic era up to the eve of the Mongol invasion.